Drugs of Abuse Differentially Alter the Neuronal Excitability of Prefrontal Layer V Pyramidal Cell Subtypes - Leyrer-Jackson, Jonna M.; Hood, Lauren E.; Olive, M. Foster (Frontiers in Cellular Neuroscience, 2021)
The medial prefrontal cortex (mPFC) plays an important role in regulating executive functions including reward seeking, task flexibility, and compulsivity. Studies in humans have demonstrated that drugs of abuse, including heroin, cocaine, methamphetamine, and alcohol alter prefrontal function resulting in the consequential loss of inhibitory control and increased compulsive behaviors, including drug seeking. Within the mPFC, layer V pyramidal cells, which are delineated into two major subtypes (type I and type II, which project to subcortical or commissurally to other cortical regions, respectively), serve as the major output cells which integrate information from other cortical and subcortical regions and mediate executive control. Preclinical studies examining changes in cellular physiology in the mPFC in response to drugs of abuse, especially in regards to layer V pyramidal subtypes, are relatively sparse. In the present study, we aimed to explore how heroin, cocaine, methamphetamine, ethanol and MDPV alter the baseline cellular physiology and excitability properties of layer V pyramidal cell subtypes. Specifically, animals were exposed to experimenter delivered (i.p.) heroin, cocaine, the cocaine-like synthetic cathinone MDPV, methamphetamine, ethanol or saline as a control once daily for five consecutive days. On the fifth day, whole-cell physiology recordings were conducted from type I and type II layer V pyramidal cells in the mPFC. Changes in cellular excitability, including rheobase (i.e. the amount of injected current required to elicit action potentials), changes in input/output curves as well as spiking characteristics induced by each substance were assessed. We found that heroin, cocaine, methamphetamine and MDPV decreased the excitability of type II cells, whereas ethanol increased the excitability of type I pyramidal cells. Together, these results suggest that heroin, cocaine, MDPV and methamphetamine reduce mPFC commissural output by reducing type II excitability, while ethanol increases the excitability of type I cells targeting subcortical structures. Thus, separate classes of abused drugs differentially affect layer V pyramidal subtypes in the mPFC, which may ultimately give rise to compulsivity and inappropriate synaptic plasticity underlying substance use disorders.